Global axis shape of magnetic clouds deduced from the distribution of their local axis orientation - Janvier, M. (2013)
Context. Coronal mass ejections (CMEs) are routinely tracked with imagers in the interplanetary space, while magnetic clouds (MCs) properties are measured locally by spacecraft. However, both imager and in situ data do not provide any direct estimation of the general flux rope properties. Aims. The main aim of this study is to constrain the global shape of the flux rope axis from local measurements and to compare the results from in-situ data with imager observations. Methods. We performed a statistical analysis of the set of MCs observed by WIND spacecraft over 15 years in the vicinity of Earth. We analyzed the correlation between different MC parameters and studied the statistical distributions of the angles defining the local axis orientation. With the hypothesis of having a sample of MCs with a uniform distribution of spacecraft crossing along their axis, we show that a mean axis shape can be derived from the distribution of the axis orientation. As a complement, while heliospheric imagers do not typically observe MCs but only their sheath region, we analyze one event where the flux rope axis can be estimated from the STEREO imagers. Results. From the analysis of a set of theoretical models, we show that the distribution of the local axis orientation is strongly affected by the overall axis shape. Next, we derive the mean axis shape from the integration of the observed orientation distribution. This shape is robust because it is mostly determined from the overall shape of the distribution. Moreover, we find no dependence on the flux rope inclination on the ecliptic. Finally, the derived shape is fully consistent with the one derived from heliospheric imager observations of the June 2008 event. Conclusions. We have derived a mean shape of MC axis that only depends on one free parameter, the angular separation of the legs (as viewed from the Sun). This mean shape can be used in various contexts, such as studies of high-energy particles or space weather forecasts. © ESO, 2013.